Development and integration of capacitive sensing and electrocuting grid for mosquitoes surveillance and control - Khoo, Brendan Teng Thiam (2020)
The survivability, prosperity and wellbeing of humankind are influenced by the insects around them. While many beneficial insects aid humans in diverse ways such as in pollination and production of honey, pest insects especially mosquitos, cause general nuisance and can carry deadly diseases. Being the deadliest group of animals in the world, mosquitos demand efficient, effective and proactive control measures to reduce the number of human casualties worldwide. For this reason, many control and surveillance techniques have been devised by researchers to monitor and suppress the population of mosquitos. However, many of these conventional methods lack automation and remote communication capability to provide a realtime and cost-effective solution for mosquito surveillance. Besides that, most of the conventional mosquito control methods could inadvertently eliminate non-target and beneficial insects in process. Therefore, Remote Automated Mosquito Control and Surveillance (RAMCS), an automated system for controlling and surveillance is designed and developed in this thesis to compliment the current conventional methods. The RAMCS system is designed as an upgrading kit for conventional control and surveillance traps to automatically identify the species of airborne insects and selectively eliminate the target species without harming the non-target species. The core functionality of the RAMCS system features the novel design of the trapping and sensing mechanism known as Smart Net which consists of only conductive grids. These conductive grids act as an insect wing-beat sensor as well as an electrocuting trap to kill or disable the target insect. This sensor design offers a very compact, robust and simple solution compared to existing optical wing-beat sensor. Other than that, the trap-cum-sensor design is more durable and simpler than electromechanical trapping mechanisms. The Smart Net module is implemented in the Smart Kit along with other supporting components of the RAMCS system: Central Server and Base Station. Smart Kit can be installed on conventional traps to convert them into smart traps with Internet of Things (IoT) functionality. The Base Station relays surveillance, control and maintenance data between the smart traps and the Central Server using cellular internet access and Long Range (LoRa) radio. The Central Server stores the surveillance data from all the smart traps and hosts web applications for users to monitor and manipulate the system. The final proposed system is tested with a basic species recognition algorithm and achieved species recognition rate of between 75% to 83% and selective trapping rate of between 63% to 69%.